Catholic Commitment Around the Globe: A 52‐ Country Analysis. Issue 2 (12th June 2018) - Conway, Brian; Spruyt, Bram
Abstract: This article investigates variation in Catholic religious commitment in different macro world regions. Although sociologists have examined variation in Catholic religiosity, this research has tended to be limited to Western European and Latin American contexts and has not gone beyond employing more than one measure of religiosity. In addition, prior research has rarely examined the effect of several explanatory frameworks together. Drawing on data from the European and World Values Survey as well as national‐level data, we test for the influence of secularization/existential security, religious markets, and historical legacies on self‐rated importance of God, private prayer, and church attendance across 52 countries in five world macro‐regional contexts—Africa, Asia, Europe, Latin America, and Oceania—of the church. Our findings provide strong support for the existential security perspective and partial support for the historical legacy perspectives. We conclude with implications for the study of religion and society in general.